Mesogenic element-containing low-melting-temperature solid additive as well as preparation method and application thereof

By developing a low melting temperature solid additive, the problem of solvent additive residue destroying the morphology of the photoactive layer is solved, and the efficient photoelectric conversion and stability improvement of organic solar cells is achieved.

CN119504497AActive Publication Date: 2025-02-25ENERGY RES INST OF JIANGXI ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411755030.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

In existing organic solar cell devices, the high boiling point of the solvent additive causes the residue to destroy the morphology of the photoactive layer, resulting in composite energy loss and manufacturing instability.

Method used

A low melting temperature solid additive containing mesogenic moieties was developed, and a solid additive with low melting temperature was prepared by heating reaction of a synthetic biphenol derivative with 1,8-dibromooctane and potassium carbonate, and used in organic solar cells.

Benefits of technology

The photoelectric conversion efficiency is improved in organic solar cells, reaching 18.3%, and the stable performance is maintained after a long period of storage, improving the stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504497A_ABST
    Figure CN119504497A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of semiconductor materials, and particularly relates to a mesogenic element-containing low-melting-temperature solid additive as well as a preparation method and application thereof. The solid additive material with low melting temperature is obtained by taking a derivative of diphenol and 1, 8-dibromooctane as main raw materials through organic synthesis, and the solid additive material is applied to an efficient organic solar cell device. Experiments show that the low-melting-temperature solid additive provided by the invention can obviously improve the performance of the device in the organic solar cell device, the photoelectric conversion efficiency far exceeding that of an additive-free binary organic solar cell is realized, the stability of the device is also obviously improved, and the low-melting-temperature solid additive has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor materials, and in particular relates to a low melting temperature solid additive containing mesogens, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] Organic solar cells (OSCs) are considered to be one of the most promising photovoltaic technologies due to their unique properties such as light weight, semi-transparency and flexibility, showing great potential for practical applications. At present, the development of material design and device engineering has enabled the power conversion efficiencies (PCEs) of single-junction organic solar cell devices to exceed 19%. Among them, the nanoscale morphology of binary or multi-component active layers composed of polymer donors and non-fullerene small molecule acceptors plays a crucial role in charge generation and transport as well as in suppressing charge recombination. In order to obtain the ideal active layer morphology with suitable domain size and molecular orientation, adding a small amount of suitable solvent additives to the main solvent is considered to be one of the most effective methods, such as 1,8-diiodooctane (DIO), diphenyl ether (DPE) and 1-chloronaphthalene (1-CN). Solvent additives have higher boiling points than the main solvent, which can promote the precise distribution and separation of donor and acceptor materials and promote optimal phase separation during film formation. However, since solvent additives usually have high boiling points, even a small amount of additive residues can destroy the desired morphology of the photoactive layer, resulting in additional recombination energy loss and reducing the reproducibility of device fabrication and its long-term stability. Therefore, it is crucial and urgent to address the above shortcomings while ensuring optimal morphology control.

[0004] Liquid crystal molecules have the properties of both crystals and liquids, exhibiting the fluidity of liquids while maintaining anisotropy and ordered aggregation. Below the phase transition temperature, they exhibit strong self-assembly properties. For example, the BTR series of small molecule donor materials contain benzodithiophene, terthiophene, and rhodamine, which are widely considered to be highly efficient nematic liquid crystals when used as the third component for preparing ternary devices. However, it should be noted that the phase transition temperature of BTR is usually too high (about 160-230°C, much higher than the thermal annealing temperature of the active layer), which limits some of its key liquid crystal properties.

[0005] Therefore, how to synthesize a solid additive with a low melting point so that it exhibits the characteristics of a liquid additive during processing while maintaining a solid state during device operation, thereby achieving the dual goals of optimizing the active layer morphology and improving device stability, is an urgent problem to be solved by technical personnel in this field. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a low melting temperature solid additive containing mesogens and a preparation method and application thereof. The additive material prepared by the present invention is simple to synthesize, low in cost and has a low melting temperature, and is applied to organic solar cell devices. By adjusting the incorporation ratio, a photoelectric conversion efficiency of 18.3% can be achieved, and the ideal photoelectric conversion efficiency can still be maintained after a long period of storage.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention provides a compound having a structure shown in Formula I or a pharmaceutically acceptable salt, solvate or hydrate thereof: Formula I; Wherein, R is selected from one of cyano, alkoxy and formate.

[0008] The second aspect of the present invention provides a low melting temperature solid additive containing mesogens, wherein the low melting temperature solid additive comprises the compound described in the first aspect.

[0009] The third aspect of the present invention provides a method for preparing the compound described in the first aspect, specifically comprising: mixing 1,8-dibromooctane, compound 1 and potassium carbonate in an organic solvent, and heating to react to obtain the compound.

[0010] Preferably, the molar ratio of the 1,8-dibromooctane, compound 1 and potassium carbonate is 7-9:1:7-9; preferably 8:1:8; the compound 1 is , R is selected from one of cyano, alkoxy and formate.

[0011] Preferably, the organic solvent is selected from one or more of acetone and N,N-dimethylformamide, preferably acetone.

[0012] Preferably, the heating reaction temperature is 50-70°C, and the time is 8-12 h; further preferably, the heating reaction temperature is 60°C, and the time is 10 h.

[0013] Preferably, the heating reaction is carried out under an inert atmosphere; further preferably, the inert atmosphere is selected from one or more of hydrogen, argon and nitrogen.

[0014] Preferably, after the heating reaction is completed, the mixture is washed with saturated brine, extracted with an organic solvent, and then the organic solvent is removed by rotary evaporation. The product is then purified using a gel chromatography column to obtain a low melting temperature solid additive containing a mesogen.

[0015] Further preferably, the organic solvent used in the extraction is selected from one of dichloromethane, ethyl acetate and chloroform, preferably dichloromethane; and the eluent used in the gel chromatography column purification is a petroleum ether / dichloromethane elution system with a volume ratio of 3:1.

[0016] The fourth aspect of the present invention provides an application of the compound described in the first aspect, the low melting temperature solid additive containing mesogens described in the second aspect and / or the compound prepared by the preparation method described in the third aspect in an organic solar cell.

[0017] The fifth aspect of the present invention provides a method for preparing a photoactive layer of an organic solar cell, comprising: mixing the compound described in the first aspect, the low melting temperature solid additive containing mesogens described in the second aspect and / or the compound prepared by the preparation method described in the third aspect with an electron donor material, an electron acceptor material and a solvent to obtain a blend; and using the blend to prepare the photoactive layer of the organic solar cell.

[0018] Preferably, the mass ratio of the compound to the electron acceptor material is 0.1-0.3:1, preferably 0.2:1; the mass ratio of the electron donor material to the electron acceptor material is 1:1-2, preferably 1:1.2.

[0019] The beneficial effects achieved by one or more technical solutions of the present invention are as follows: (1) The present invention uses biphenol derivatives and 1,8-dibromooctane as main raw materials, obtains a solid additive material with a low melting temperature through organic synthesis, and applies it in high-efficiency organic solar cell devices. Experiments show that the low melting temperature solid additive provided by the present invention can significantly improve the device performance in organic solar cell devices, achieve a photoelectric conversion efficiency far exceeding that of additive-free binary organic solar cells, and the device stability is also significantly improved.

[0020] (2) The synthesis method of the present invention is simple, efficient, and reproducible, low-cost, universal, and easy to scale up for production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1This is the hydrogen nuclear magnetic resonance spectrum of the low melting temperature solid additive material CB8-Br prepared in Example 1 of the present invention; Figure 2 The performance test diagram of the organic solar cell device prepared in Experimental Example 1 of the present invention, wherein (a) is a JV curve diagram, and (b) is an external quantum efficiency diagram; Figure 3 The performance test diagrams of organic solar cell devices with different amounts of additive CB8-Br prepared in Experimental Examples 1 to 3 of the present invention, wherein (a) is a JV curve diagram, and (b) is a device stability test curve; Figure 4 The performance test diagram of the organic solar cell device prepared in Experimental Example 4 of the present invention, wherein (a) is a JV curve diagram, and (b) is an external quantum efficiency diagram; Figure 5 The optical and electrical performance analysis diagrams of the low melting temperature solid additive material CB8-Br prepared in Example 1 of the present invention; wherein, (a) is a UV-visible absorption comparison spectrum of the CB8-Br solution and the film, (b) is a UV-visible absorption comparison spectrum before and after the addition of the organic solar cell active layer additive, (c) is a cyclic voltammetry curve of CB8-Br, and (d) is a differential scanning calorimetry analysis curve of CB8-Br. DETAILED DESCRIPTION

[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0024] The first typical embodiment of the present invention provides a compound having a structure shown in Formula I or a pharmaceutically acceptable salt, solvate and hydrate thereof: Formula I; Wherein, R is selected from one of cyano, alkoxy and formate.

[0025] A second typical embodiment of the present invention provides a low melting temperature solid additive containing mesogens, wherein the low melting temperature solid additive comprises the above-mentioned compound.

[0026] A third typical embodiment of the present invention provides a method for preparing the above compound, specifically comprising: mixing 1,8-dibromooctane, compound 1 and potassium carbonate in an organic solvent, and heating to react to obtain the compound.

[0027] In one or more examples of this embodiment, the molar ratio of 1,8-dibromooctane, compound 1 and potassium carbonate is 7-9:1:7-9; preferably 8:1:8; the compound 1 is , R is selected from one of cyano, alkoxy and formate.

[0028] In one or more examples of this embodiment, the organic solvent is selected from one or more of acetone and N,N-dimethylformamide, preferably acetone.

[0029] In one or more examples of this embodiment, the temperature of the heating reaction is 50-70° C., and the time is 8-12 h; more preferably, the temperature of the heating reaction is 60° C., and the time is 10 h.

[0030] In one or more examples of this embodiment, the heating reaction is carried out under an inert atmosphere; further preferably, the inert atmosphere is selected from one or more of hydrogen, argon, and nitrogen.

[0031] In one or more examples of this implementation mode, after the heating reaction is completed, the product is washed with saturated brine, extracted with an organic solvent, and then the organic solvent is removed by rotary evaporation. The product is then purified using a gel chromatography column to obtain a low melting temperature solid additive containing a mesogen.

[0032] In one or more examples of this embodiment, the organic solvent used for the extraction is selected from one of dichloromethane, ethyl acetate and chloroform, preferably dichloromethane; the eluent used for the gel chromatography column purification is a petroleum ether / dichloromethane elution system with a volume ratio of 3:1.

[0033] A fourth typical embodiment of the present invention provides a use of the above compound, the low melting temperature solid additive containing mesogens and / or the compound prepared by the above preparation method in an organic solar cell.

[0034] A fifth typical embodiment of the present invention provides a method for preparing a photoactive layer of an organic solar cell, comprising: mixing the above-mentioned compound, a low melting temperature solid additive containing a mesogen and / or a compound prepared by the above-mentioned preparation method with an electron donor material, an electron acceptor material and a solvent to obtain a blend; and using the blend to prepare the photoactive layer of the organic solar cell.

[0035] In one or more examples of this embodiment, the mass ratio of the compound to the electron acceptor material is 0.1-0.3:1, preferably 0.2:1; the mass ratio of the electron donor material to the electron acceptor material is 1:1-2, preferably 1:1.2.

[0036] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0037] Example 1 :This embodiment provides a low melting temperature solid additive material CB8-Br The synthesis method is as follows:

[0038] The specific synthesis steps include: 4'-cyano-4-hydroxybiphenyl (0.5 g, 2.56 mml, 1.0 eq) and 1,8-dibromooctane (5.57 g, 20.48 mmol, 8.0 eq) were added to the two-necked reaction bottle in sequence. Potassium carbonate (2.83 g, 20.48 mmol, 8.0 eq) was used to provide an alkaline environment for the reaction. Ultra-dry acetone was used as the solvent. The mixture was heated to reflux at 60°C under nitrogen protection for 10 h. After the reaction, the mixture was washed with saturated brine, extracted with dichloromethane three times, the organic phases were combined, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by rotary evaporation. Column chromatography was used for separation and purification (petroleum ether: dichloromethane = 3:1). The additive CB8-Br was obtained as a light yellow solid of 0.86 g with a yield of 86.9%; 1 H NMR (400 MHz, CDCl3) δ 7.66 (dd, J = 21.0, 8.6 Hz, 4H), 7.53 (d, J = 8.8 Hz, 2H), 6.99 (d, J = 8.8 Hz, 2H), 4.01 (t, J = 6.5 Hz, 2H), 3.41 (t, J = 6.8 Hz, 2H), 1.92-1.77 (m, 4H), 1.52-1.34 (m, 8H). The specific H NMR spectrum is shown in the figure. Figure 1 shown.

[0039] Test Example 1 :This experimental example provides the application of low melting temperature solid additive material CB8-Br in the preparation of organic solar cells This experimental example adopts a single-layer device structure of ITO / PEDO:PSS / photoactive layer / HPDIN-B02 / Ag, wherein ITO is a transparent conductive electrode, PEDOT:PSS is a hole transport layer, HPDIN-B02 is an electron transport layer, the photoactive layer is composed of a blend of electron donor PM6 and electron acceptor L8-BO, and the additive CB8-Br is used in the preparation process of the photoactive layer film.

[0040] The structure of the donor material PM6 and the acceptor material L8-BO is as follows:

[0041] The process of preparing organic solar cells using low melting temperature solid additive materials is as follows: First, the device substrate ITO glass was cleaned and dried, and then treated in a UV cleaner for 15 minutes before use. Then, the hole transport layer material PEDOT:PSS was spin-coated on the ITO substrate using a spin coater at a speed of 4000 rpm and annealed at 200°C for 15 minutes to form a uniform film. After annealing, the sample was transferred to a nitrogen glove box and the prepared photoactive layer solution was spin-coated on the hole transport layer. The photoactive layer solution was a blend of CB8-Br, PM6 and L8-BO dissolved in a chloroform solution, and the concentration of the blend was 15 mg / mL (PM6: L8-BO = 1:1.2, mass ratio). The amount of additive CB8-Br was 20% of the acceptor mass, the speed was 3000 rpm / min, the time was 30 s, and the thickness of the photoactive layer was 90nm. The photoactive layer was annealed at 80°C for 5 min, and then the electron transport layer solution HPDIN-B02 (2 mg / mL) was spin-coated at 3500 rpm, and finally a 100 nm Ag electrode was evaporated to obtain an organic solar cell. At the same time, when preparing the donor and acceptor blend solution, no solid additives were added, and an organic solar cell for control was prepared in parallel.

[0042] In a nitrogen-filled glove box, a AAA-class solar simulator (AM 1.5G, 100 mW cm -2 ) irradiated the prepared organic solar cell under the optimal conditions of the device (test area is 0.0289 cm 2 ) was used to test the voltage-current curve (JV curve of the device), and the parameters were measured as shown in Table 1.

[0043] Table 1

[0044] As shown in Table 1, the photoelectric conversion efficiency of a single-cell organic solar cell device with PM6 and L8-BO as the photoactive layer is generally 16.59% without using additives. However, after using CB8-Br as an additive in the present invention, the photoelectric conversion efficiency of the organic solar cell device is 18.12%, reaching the world's leading level in this field, proving that the material has potential application value in organic solar cells.

[0045] Depend on Figure 2As can be seen in Figure (a), compared with the PM6:L8-BO binary device without additives, after adding CB8-Br, although the open circuit voltage is reduced to a certain extent, the short-circuit current density and fill factor are significantly improved, and the device efficiency has increased from 16.59% to 18.12%. In the external quantum efficiency diagram, the error between the short-circuit current density value corrected by EQE and the short-circuit current value of the device is within 95%, which also confirms the reliability of the short-circuit current density (such as Figure 2 (as shown in Figure (b)).

[0046] Test Example 2 :This experimental example provides the application of low melting temperature solid additive material CB8-Br in the preparation of organic solar cells The difference between this test example and test example 1 is that the amount of additive CB8-Br is 10% of the acceptor mass, and the other experimental conditions and test processes are the same. From the device test results, it can be seen that after the introduction of 10% CB8-Br, the short-circuit current density and fill factor of the device are significantly improved, and the photoelectric conversion efficiency is significantly improved. The measured parameters are shown in Table 2.

[0047] Table 2

[0048] Test Example 3 :This experimental example provides the application of low melting temperature solid additive material CB8-Br in the preparation of organic solar cells The difference between this test example and test example 1 is that the amount of additive CB8-Br is 40% of the acceptor mass, and the other experimental conditions and test processes are the same. From the device test results, it can be seen that after the introduction of 40% CB8-Br, the various parameters of the device dropped sharply, and the photoelectric conversion efficiency was less than 1%, indicating that the amount of additive has exceeded the maximum value of device preparation. The measured parameters are shown in Table 3.

[0049] Table 3

[0050] Test Example 4 :This test example performs a performance comparison test on the organic solar cell devices prepared in Test Examples 1 to 3 from Figure 3 As can be seen in Figure (a), by adjusting the amount of additive CB8-Br added, gradually increasing it from 10% to 30% relative to the mass of the electron acceptor material, the photoelectric conversion efficiency of the device has a significant increase followed by a decrease, and the best photoelectric conversion efficiency is achieved when the introduction amount is 20%. Therefore, effective regulation of the performance of organic solar cell devices can be achieved.

[0051] from Figure 3As can be seen from Figure (b), the battery device using CB8-Br (the amount of CB8-Br added is 20% of the acceptor mass) can still maintain more than 96% of the initial photoelectric conversion efficiency after more than 900 hours, showing excellent device stability.

[0052] Test Example 5 :This experimental example provides the application of low melting temperature solid additive material CB8-Br in the preparation of organic solar cells This experimental example adopts a single-layer device structure of ITO / PEDO:PSS / photoactive layer / HPDIN-B02 / Ag, wherein ITO is a transparent conductive electrode, PEDOT:PSS is a hole transport layer, HPDIN-B02 is an electron transport layer, the photoactive layer is composed of a blend of electron donor PM6 and electron acceptor BTP-eC9, and the additive CB8-Br is used in the preparation process of the photoactive layer film.

[0053] Among them, the receptor material is BTP-eC9, and its structure is as follows:

[0054] The process of preparing organic solar cells using low melting temperature solid additive materials is as follows: First, clean and dry the device substrate ITO glass, and then treat it in a UV cleaner for 15 min before use. Use a spin coater to spin coat the hole transport layer material PEDOT:PSS on the ITO substrate at a speed of 4000 rpm and anneal at 200°C for 15 min to form a uniform film. After annealing, transfer the sample to a nitrogen glove box and spin coat the prepared photoactive layer solution on the hole transport layer, where the photoactive layer solution is a blend of CB8-Br, PM6 and BTP-eC9 dissolved in a chloroform solution, so that the concentration of the blend is 15 mg / mL (PM6:BTP-eC9 =1:1.2, mass ratio), where the amount of additive CB8-Br is 20% of the receptor mass, the rotation speed is 3500 rpm / min, the time is 30 s, and the active layer thickness is 90 nm. The active layer was annealed at 80 °C for 5 min, and then the electron transport layer solution HPDIN-B02 (2 mg / mL) was spin-coated at 3500 rpm, and finally a 100 nm Ag electrode was evaporated. At the same time, when preparing the donor and acceptor blend solution, no solid additives were added, and an organic solar cell for control was prepared in parallel.

[0055] In a nitrogen-filled glove box, a AAA-class solar simulator (AM 1.5G, 100 mW cm -2 ) irradiated the prepared organic solar cell under the optimal conditions of the device (test area is 0.0289 cm 2) was used to test the voltage-current curve, and the parameters were measured as shown in Table 4.

[0056] Table 4

[0057] As shown in Table 4, the photoelectric conversion efficiency of a single-cell organic solar cell device with PM6 and BTP-eC9 as the photoactive layer is 17.18% without using additives. However, after using CB8-Br as an additive in the present invention, the photoelectric conversion efficiency of the organic solar cell device is 18.38%, reaching the world's leading level in this field.

[0058] Depend on Figure 4 As can be seen in Figure (a), compared with the PM6:BTP-eC9 binary device without additives, after adding CB8-Br, although the open circuit voltage is reduced to a certain extent, the short-circuit current density and fill factor are significantly improved, and the device efficiency has increased from 17.18% to 18.38%. In the external quantum efficiency diagram, the error between the short-circuit current density value corrected by EQE and the short-circuit current value of the device is within 95%, which also confirms the reliability of the short-circuit current density (such as Figure 4 (as shown in Figure (b)).

[0059] Test Example 6 :This test example tests the optical and electrochemical properties of CB8-Br and PM6 and L8-BO blended films. Depend on Figure 5 As can be seen from Figure (a), the solution absorption spectrum of CB8-Br is distributed in the range of 250-340 nm, with the highest absorption peak at 298 nm, while its film absorption is red-shifted, with the maximum absorption peak at 308 nm (film preparation: using chloroform as solvent, a 15 mg / mL solution is prepared, and spin-coated on a quartz substrate at a rotation speed of 1500 rpm / min).

[0060] Depend on Figure 5 As can be seen from Figure (b), by comparing the UV-visible absorption spectra of the organic solar cell active layer before and after the addition of the additive CB8-Br, it can be found that after the addition of CB8-Br (the amount of CB8-Br added is 20% of the acceptor mass), the absorption of the photoactive layer film undergoes an obvious overall red shift, and the absorption coefficient of the acceptor part also increases to a certain extent (650~900 nm), which are all conducive to the device to obtain a higher short-circuit current density and ultimately improve the photoelectric conversion efficiency (preparation of the photoactive layer film: using chloroform as the solvent, preparing a 12 mg / mL solution, and spin coating it on a quartz substrate at a rotation speed of 2500 rpm / min).

[0061] Depend on Figure 5As can be seen in Figure (c), the cyclic voltammetry curve shows that the highest unoccupied molecular orbital (HOMO) of CB8-Br is -5.93 eV, while the lowest occupied molecular orbital (LUMO) is -3.61 eV.

[0062] Depend on Figure 5 As can be seen from Figure (d) in the figure, the melting temperature of CB8-Br is 80.1℃ from the differential scanning calorimetry test analysis.

[0063] At present, the annealing temperature of the active layer of most high-efficiency organic solar cells is distributed between 80-100°C, especially for the PM6:L8-BO system and PM6:BTP-eC9 system with PCE exceeding 19%, the annealing temperature is exactly 80°C. This means that when the active layer containing CB8-Br is annealed, CB8-Br optimizes the morphology of the active layer in liquid form, and when the device is working normally, it exists in the active layer in solid form, which is conducive to maintaining a stable active layer morphology, thereby improving device stability.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A compound, characterized in that The compound has a structure shown in Formula I or a pharmaceutically acceptable salt, solvate or hydrate thereof: Formula I; Wherein, R is selected from one of cyano, alkoxy and carboxylate.

2. A low melting temperature solid additive containing mesogens, characterized in that: The low melting temperature solid additive comprises the compound according to claim 1.

3. A method for preparing the compound according to claim 1, characterized in that: Specifically, 1,8-dibromooctane, compound 1 and potassium carbonate are mixed in an organic solvent, and heated to react to obtain the product.

4. The preparation method according to claim 3, characterized in that: The molar ratio of 1,8-dibromooctane, compound 1 and potassium carbonate is 7-9:1:7-9; preferably 8:1:8; the compound 1 is , R is selected from one of cyano, alkoxy and formate; the organic solvent is selected from one or more of acetone and N,N-dimethylformamide, preferably acetone.

5. The preparation method according to claim 3, characterized in that: The temperature of the heating reaction is 50-70°C, and the time is 8-12 h; preferably, the temperature of the heating reaction is 60°C, and the time is 10 h.

6. The preparation method according to claim 3, characterized in that: The heating reaction is carried out under an inert atmosphere; preferably, the inert atmosphere is selected from one or more of hydrogen, argon and nitrogen.

7. The preparation method according to claim 3, characterized in that: After the heating reaction is completed, the mixture is washed with saturated brine, extracted with an organic solvent, and then the organic solvent is removed by rotary evaporation. The product is then purified by a gel chromatography column to obtain a low melting temperature solid additive containing a mesogen; The organic solvent used in the extraction is selected from one of dichloromethane, ethyl acetate and chloroform, preferably dichloromethane; the eluent used in the gel chromatography column purification is a petroleum ether / dichloromethane elution system with a volume ratio of 3:

1.

8. Use of the compound according to claim 1, the low melting temperature solid additive containing mesogens according to claim 2, and / or the compound prepared by the preparation method according to any one of claims 3 to 7 in an organic solar cell.

9. A method for preparing a photoactive layer of an organic solar cell, characterized in that: include: The compound according to claim 1, the low melting temperature solid additive containing mesogens according to claim 2 and / or the compound prepared by the preparation method according to any one of claims 3 to 7 are mixed with an electron donor material, an electron acceptor material and a solvent to obtain a blend; and the blend is used to prepare the photoactive layer of the organic solar cell.

10. The method according to claim 9, characterized in that The mass ratio of the compound to the electron acceptor material is 0.1-0.3:1, preferably 0.2:1; The mass ratio of the electron donor material to the electron acceptor material is 1:1-2, preferably 1:1.2.

Citation Information

Patent Citations

  • Solid additive, organic solar cell active layer containing same and application

    CN118401081A

  • Application of solid additive in organic solar cell and cell preparation method

    CN118890906A

  • Optically active biphenyl compound, production thereof, liquid crystal composition containing the same and liquid crystal element using the same

    JP1990152953A

  • Processing Additives for Fabricating Organic Photovoltaic Cells

    US20090108255A1